Training Professionalism Using Hidden Curriculum in an Internship Course: Account of Experiences of Undergraduate Students of Surgical Technology - Leila Jouybari; Fereshte Araghian Mojarad; Mehri Behmadi; Nadia Shirazi; Maryam Chehrehgosha; Soheyla Kalantary (Kerman University of Medical Sciences, 2018)
Background Medical students are in direct contact with patients due to their clinical situation, and one of the important goals of medical education is professional development of these students. Objectives The purpose of this study was to explain students' experiences regarding professionalism training using hidden curriculum. Methods This study was carried out through content analysis, and data were collected through semi-structured interviews with 6th and 8th semester undergraduate students of surgical technology. The participants were entered into the study using the purposive sampling method and each individual interview lasted for about 35 - 45 minutes. Semi-structured questions were used to conduct the interviews and then follow-up and exploratory questions were used to clarify the concept and to deepen the interview process. Results Overall, 358 primary codes and the two main themes of observing patient rights and professional accountability were extracted. The theme of observing patient rights includes three sub-themes, including observing patient privacy, respect for patient's dignity and patient safety, and the theme of professional accountability comprised the three sub-themes of compliance with professional standards, professional communication and instructor as ethics teacher. Conclusions Professors' familiarity with the training and development of professionalism among medical students, and attention to the role of hidden curriculum in the formulation of values, norms and behaviors regarding professionalism is suggested.